IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENT'S CRITICAL THINKING ABILITY IN TWO VARIABLE LINEAR EQUATION SYSTEM MATERIALS - Andika Kusuma Wijaya; Sayaka Oikawa; Miao Miao (Journal of Educational Review and Research, 2023)
The aim of the research is to find out the application of the problem based learning model to students' critical thinking skills. The type of research used is quantitative. The research design used was the One Group Pretest-Posttest Design. The results of the implementation research using the problem based learning model showed that at the first meeting 75.93% had good criteria and 85.19% the second meeting had very good criteria, the results of data analysis using the t-test, obtained a t_count value of 6.60 and a t_table of 2.045 with a significant level of 5%, because (t_count > t_table) it can be said that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So it can be said that the application of the problem based learning model can improve students' critical thinking skills. The calculation of the completeness of student learning outcomes after using the problem based learning model is 82.76% above the specified classical completeness of 70%. The results of the student response questionnaire calculations as a whole gave a positive response to the problem based learning model in the material of the Two Variable Linear Equation System (SPLDV) which was applied ranging from good to very good criteria.